Analysis of "The Tradition of Ruwatan Wayang" in Culture Preservation as an Effort to Form a Tourist Village in Sukoanyar Lamongan Village - Nurus Safa'atilllah; Iva Milatul Chanifah (Enrichment : Journal of Management, 2021)
One of the cultures that we want to promote in this study is the tradition of ruwatan wayang which is held by the community and members of the village of Sukoanyar. The tradition that is held every year always gets enthusiasm from the community, because in addition to this tradition which is only carried out once a year, this tradition also brings many positive things that will be accepted by the community. Ruwatan wayang is a tradition passed down from generation to generation from ancestors who believe in mystical things. The results of the questionnaire for residents focused on the understanding of tourism villages and exploring the village's potential according to the respondents directly, namely (1) the meaning of tourism villages, (2) the purpose of developing a tourist village, (3) village conditions, (4) village community responses to tourism villages, (5) the type of tourism that the community wants, (6) the form of community participation in the development of a tourism village, and (7) the development of facilities needed by the village as well as a critique and suggestion rubric if the community wants to add ideas and ideas that are not yet in the questionnaire choice. The people basically agree with the formation of a tourist village that has a distinctive village nuance, the aim of developing a tourist village is to provide a community forum to play a role and participate in tourism development in their area because people have various opinions regarding the condition of Sukoanyar village, some say it is cool and quite beautiful, but there are some who say normal so that it can be saved In fact, the condition of Sukoanyar village is actually normal so that to form a Sukoanyar tourism village through agricultural, plantation and cultural tourism through educational tours with the form of local community participation to organize and manage tours and facilities that need to be developed in Sukoanyar village are facilities for trading, parking, culinary , souvenirs and places of worship.